Abortion, or an everlasting problem with/for women? - Mencin Čeplak, Metka (Teorija in praksa, 2016)
Abortion and the legal regulation of access to abortion are even these days a matter of numerous trivial, scientific and theoretical discussions. The first part of the article aims to present the feminist perspective on abortion and the fundamental discrepancies that are thematised in feminist debates. This is followed by an analysis of critical discursive moments that have made the abortion issue visible and stimulated public debates: it focuses on anti-abortion discourses in Slovenia from the mid-1980s to September 2016. The author establishes that these discourses derive from the same interconnected ideological contexts (nationalism, patriarchy, heteronormativity, biologism, anti-socialism, anti-communism), although they have started to grow in number since the early 2000s, together with topics and the audiences to which they are addressed (strategies of the interpellation of women are especially indicative).
Keywords: Abortion; Analiza diskurza; Discourse analysis; Feminism; Feminizem; Nacionalizem; Nationalism; Slovenia; Slovenija; Splav; splav (medicina)